(untitled) (Sociología y tecnociencia, 2023)
The Unitary State of the Republic of Indonesia has one of the primary objectives to realize the welfare of the people, while a welfare state focuses on equitable distribution to the community.Regulating the separated state finances as capital in state-owned enterprises is very important for developing the country’s economy.The problem often occurs that many of the directors of state-owned enterprises caught for corruption cases have caused losses to the state due to the unclear position of state finances in those organizations. The research was a normative one through the prevailing laws and regulations. Also, the separated state assets will be the wealth of state-owned enterprises, so the loss belongs solely to the state-owned enterprises